Coral reef flounders, Bothus lunatus, choose substrates on which they can achieve camouflage with their limited body pattern repertoire. (30th December 2014) - Tyrie, Elizabeth K.; Hanlon, Roger T.; Siemann, Liese A.; Uyarra, Maria C.
<x xml:space="preserve">Abstract</x> Camouflage is a common tactic to avoid detection or recognition by predators and prey. Flounders have adaptive camouflage but a limited body pattern repertoire. We tested whether peacock flounders actively select or avoid certain substrates to more effectively use their limited camouflaging ability. We acquired and analyzed ten 30‐min videos of individual flounders on a coral reef in Bonaire, Dutch Caribbean. Using Manly's beta resource selection indices, we were able to confirm that peacock flounders at this location preferred to settle on neutral‐coloured substrates, such as sand and dead coral. Moreover, they avoided live coral, cyanobacteria, and sponges, which are often brightly coloured (e.g. yellow, orange, and purple). Quantitative analyses of photographs of settled flounders indicate that they use uniform and mottled camouflage patterns, and that the small‐to‐moderate spatial scale of their physiologically controlled light and dark skin components limits their camouflage capabilities to substrates with similar colour and spatial frequencies. These fishes changed their body pattern very fast. We did not observe disruptive body patterns, which are generally characterized by large‐scale skin components and higher contrast. The results suggest that flounders are using visual information to actively choose substrates on which they can achieve general background resemblance. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 629–638.